Fatal Journey: Acute Liver Failure as a Complication of Nasal NK/T-Cell Lymphoma in a 53-Year-Old Male - Lia Sasmithae; Silverius Seantoni Sabela (Jurnal Impresi Indonesia, 2025)
Acute liver failure is a rare but catastrophic complication in nasal-type NK/T-cell lymphoma, typically occurring in terminal stages and associated with mortality rates nearing 94%. This report describes a 53-year-old male with NKTCL who developed ALF after his third cycle of Gemox chemotherapy, presenting with severe right upper quadrant pain, rapid jaundice, and diffuse bruising. Laboratory findings showed marked hepatic injury with extreme transaminitis, hyperbilirubinemia, hypoalbuminemia, and thrombocytopenia, while ultrasound revealed hepatomegaly and multiple complex masses consistent with extensive malignant hepatic infiltration. The ALF was determined to result from a dual mechanism: direct lymphoma infiltration combined with chemotherapy-induced hepatotoxicity, creating a synergistic injury that overwhelmed hepatic function. Despite aggressive supportive care, the patient deteriorated rapidly and died shortly after the onset of liver failure. This case underscores the highly aggressive course of NKTCL complicated by hepatic involvement and highlights the need for strict liver function monitoring during systemic therapy, as transplantation is generally contraindicated and therapeutic options remain extremely limited